Publisher Correction: Unravelling the immune signature of Plasmodium falciparum transmission-reducing immunity - Will J. R. Stone (Nature Portfolio, 2018)
The original version of this Article contained errors in Fig. 3. In panel a, bars from a chart depicting the percentage of antibody-positive individuals in non-infectious and infectious groups were inadvertently included in place of bars depicting the percentage of infectious individuals, as described in the Article and figure legend. However, the p values reported in the Figure and the resulting conclusions were based on the correct dataset. The corrected Fig. 3a now shows the percentage of infectious individuals in antibody-negative and -positive groups, in both the PDF and HTML versions of the Article. The incorrect and correct versions of Figure 3a are also presented for comparison in the accompanying Publisher Correction as Figure 1. The HTML version of the Article also omitted a link to Supplementary Data 6. The error has now been fixed and Supplementary Data 6 is available to download.